Determining the influence of working fluid temperature change on the characteristics of a single-chamber hydrostatic bearing at different values of design parameters - Nazin, Vladimir (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is hydrostatic processes in a single-chamber hydrostatic bearing of an aviation gear-type pump. The task addressed is the influence of design parameters of a single-chamber bearing on its characteristics, taking into account changes in the temperature of the working fluid. The main characteristics considered are the carry-load capacity and flow rate of the working fluid. Determining these characteristics is associated with the joint solution of the Reynolds equations and the flow balance. The basic characteristics of the hydrostatic bearing were determined on the basis of the obtained pressure distribution function in the working fluid layer. The influence of the eccentricity and diameter of the hydrostatic bearing on its characteristics has been studied, taking into account changes in the temperature of the working fluid. It was found that at zero eccentricity the temperature of the working fluid increased by 5.6 °C and was 105.6 °C. At an eccentricity of 0.018 mm, the temperature of the working fluid increased by 15.6 °C and was 115.6 °C. With an increase in eccentricity from 0 mm to 0.018 mm, the maximum increase in the working fluid consumption in a single-chamber hydrostatic bearing due to an increase in temperature was 19 %. The maximum decrease in the bearing load carrying capacity due to an increase in the working fluid temperature was 17 %; and at a working eccentricity of 0.018 mm, it did not exceed 1.83 %. With an increase in the bearing diameter, the working fluid temperature increased. At a bearing diameter of 14.5 mm, the increase in the working fluid temperature was 4.59 °C; and at a diameter of 43.5 mm, the working fluid temperature increased by 15.6 °C. The results demonstrate that an increase in the working fluid temperature with an increase in eccentricity and bearing diameter has a negligible effect on its load carrying capacity and working fluid consumption